Computational characterisation of microwave heating of fibre preforms for CVI of SiCf/SiC composites. Issue 5 (May 2023) - Porter, Matthew T.; Binner, Jon; Cinibulk, Michael K.; Stern, Kevin E.; Yakovlev, Vadim V.
Abstract: Silicon carbide fibre reinforced silicon carbide matrix composites (SiCf /SiC) are known as materials with high-performance mechanical properties for the aerospace industry. Microwave-enhanced (ME) chemical vapour infiltration (CVI) heating of ceramic matrix composites is potentially an energy efficient production technique capable of yielding near fully dense SiCf /SiC composites in a much shorter time span. This paper reports on the output of computational analysis of electromagnetic (EM) and thermal characteristics of the ME CVI process occurring with thin circular SiC fibre preform in a Labotron microwave system from SAIREM. Computer simulation is performed with the use of the finite-difference time-domain technique implemented in QuickWave computational environment. Multiple puzzling phenomena observed in the earlier experimental work are illuminated in the present study and the causes for the formation of microwave-induced temperature fields are clarified. With the use of the developed EM model, resonant and non-resonant frequencies of the Labotron system for different temperatures of the processed samples are analysed to explain the differences and variability in heating rates. This showed that when microwave processing of small SiC samples, energy coupling is extremely sensitive to frequency: a change of the reflection coefficient from 0.05 (absorbing) to 0.75 (reflective) could be made by a drift as small as 0.003–0.005 GHz, respectively, indicating the importance of scaling the microwave cavity to the sample size and the ability to precisely control the frequency of the microwave source. Moreover, energy coupling is temperature-dependent: low reflections produces very high heating rates (greater than 550 ℃ min -1 ); the opposite is true for high reflections where heating rates are significantly slower. Temperature fields in the SiC fibre preforms are computed with the coupled EM-thermal model at different frequencies. It is shown that while being highly non-uniform in the beginning of the process, temperature patterns evolve to being fairly homogeneous by its end. Overall, the results suggest a means for better control of the equipment to pave the way to more efficient, controlled, and repeatable implementations of the ME CVI technology to produce high quality SiCf /SiC composites.